Implementation of a Web-Based Management Information System for Monitoring Sales and Stock of Goods in MSMEs - Rahmah, Ummiati; Awaliyah, Neneng; Iskandar, Akbar; Ruth, Ruth (Yayasan Cendekiawan Digital Indonesia, 2026)
Digital transformation is crucial for Micro, Small, and Medium Enterprises (MSMEs) to improve business management effectiveness and competitiveness in the digital economy. However, most MSMEs still rely on manual transaction recording and inventory management, leading to operational constraints such as data entry errors, delays in preparing sales reports, and difficulties with real-time inventory monitoring. This community service activity aims to implement a web-based management information system to support sales monitoring and inventory management at Lasari Kopi MSME in Makassar City. The novelty of this activity lies in integrating sales monitoring, automated transaction recording, and real-time inventory management into a single web-based dashboard tailored to the operational needs of small-scale MSMEs. The implementation method uses an implementative-participatory approach through the stages of identifying partner needs, system development, application implementation, user training, and system evaluation. The evaluation was conducted using Black Box Testing and the System Usability Scale (SUS), with 15 respondents, including business owners and MSME employees. The implementation results show that all system features function as intended, with no functional errors. Furthermore, the usability evaluation achieved a SUS score of 89.4, which is considered Excellent. The system implementation also successfully improved business operational efficiency by accelerating the transaction recording process from an average of 4–5 minutes to 1–2 minutes and improving the accuracy of real-time inventory monitoring. Thus, the implementation of a web-based management information system has proven to support the digital transformation of MSMEs by improving administrative effectiveness, operational efficiency, and more integrated and sustainable business data management.